LEGAL ISSUES FOR THE PROTECTION OF TRADEMARK’S GOODWILL - Ավագյան Նարինե (State and Law, 2021)
The article is dedicated to the issue of legal protection of the goodwill of trademark. At present, some trademarks are able to attract consumers with their distinctive character, which is a result not of the origin of the given mark, but of the latter’s goodwill. The article deals with the functions of trademarks, especially the advertising function, which provides protection to the goodwill of the trademark. The article discusses all the justifications that underlie the protection of a goodwill of the trademark .